Design and Integration of a Robotic Welding Parameterized Procedure for Industrial Applications - Puthussery, Sangeeth; Secco, Emanuele Lindo (Universitas Ahmad Dahlan, 2024)
This paper explores the development of an effective motion planning strategy for robotics welding in tube to tubesheet joints, a critical process in heat exchanger manufacturing. The research methodology follows an experimental paradigm, investigating two distinct approaches to tackle the intricacies of this task. The initial approach, involving a welding torch affixed to the robotic arm's flange, proved ineffective due to the complexity of continuous 360° orbital welding. This led to the adoption of a custom end effector in the second approach, designed to enhance adaptability and precision. Key tools and materials employed in this research include the Robot Operating System (ROS), Rviz for 3D visualization, MoveIt for motion planning, SolidWorks for CAD modelling, and the xArm7 Robotic Arm. These tools facilitated the creation of a comprehensive planning environment. The motion planning process relies on three essential parameters: tube diameter, type of tube to tubesheet joint (flush or protruding), and the 3D coordinates of tube centers. A Python scripts control the robot's movements, with specific joint state and pose goals for precise positioning. Finally, this study contributes to present a program that orchestrates the robotic arm's motion, simulating the welding process for tube to tubesheet joints. This comprehensive research endeavor contributes to the optimization of motion planning strategies in the context of tube to tubesheet welding, with practical applications in the manufacturing industry.